Designing a Web-Based Archive Management Application Using the Laravel Framework: A Case Study on a Recreational Park - Ramadhani, Risky (SAN Scientific, 2024)
Effective archive management is one of the main needs in supporting organizational operations, including in recreational parks that have a high volume of administrative documents. This research aims to design and implement a web-based archive management application using the Laravel framework to improve efficiency in archive storage, management, and search. The research approach involves the stages of needs analysis, system design, application development, and trials on a real work environment in a recreational park. The results of the application design show that the use of Laravel as the main framework allows for the development of a responsive, secure, and easy-to-use system. The main features implemented include digital archive storage, grouping by category, keyword-based search, and role-based user access management. Testing using the black-box testing method shows that the system functions according to the designed specifications. Based on user feedback, this application is able to reduce the time of searching archives by up to 45% compared to the previous manual method. In conclusion, this Laravel-based archive management application provides a significant solution to improve the efficiency and security of document management in amusement parks. Further research is suggested to integrate the system with cloud computing technology to support more flexible access and higher scalability.